Journalistic Framing of Finnish Ice Hockey Club Jokerit in the Russian-Led Kontinental Hockey League - Joakim Särkivuori; Antti Laine (Media and Communication, 2024)
One of the major franchises in Finland’s top division in men’s ice hockey (Liiga), Jokerit Helsinki, sold its home arena and half of its shares to Finnish-Russian oligarchs in 2013. Jokerit also switched to the Russian-led Kontinental Hockey League (KHL) and competed there from 2014 to 2022. Russia’s KHL project and its expansion to the West can be viewed as a form of soft power. This study delves into the journalistic coverage of Jokerit during two specific periods: Its early days in the KHL and its later stages when exiting the league. These periods coincide with critical geopolitical events, such as Russia’s annexation of Crimea (2014), Belarusian protests (2020–2021), and Russia’s invasion of Ukraine (2022). Our data consists of Jokerit-related articles in the newspaper Helsingin Sanomat as well as interviews of the journalists who followed the team closely. We explore the critical socio-political coverage of Jokerit in Helsingin Sanomat during these periods and investigate whether the sports journalists recognized the broader geopolitical context of the KHL project and, if so, how this influenced their reporting. Utilizing the framing theory, we identified five frames under which to divide the articles: (a) sports events, (b) international relations, (c) power and governance, (d) business, and (e) unity. The sports event frame predominated during the early KHL era, whereas international relations and power and governance frames only emerged later. These shifts were not initiated by sports journalists but resulted from the efforts of journalists in other fields and increased the societal scrutiny of ties to Russia.